First genetic evidence for the presence of the rumen fluke Paramphistomum epiclitum in Pakistan. Issue 5 (October 2018) - Ali, Qasim; Rashid, Imran; Shabbir, Muhammad Zubair; Akbar, Haroon; Shahzad, Kashif; Ashraf, Kamran; Sargison, Neil; Chaudhry, Umer
Abstract: More than 70 species of the Superfamily Paramphistomoidea, have been identified in ruminants in different parts of the world. Most are pathogenic, causing amphistomosis. Adult flukes within this family have a predilection for the forestomach (rumen) or bile duct of the liver, where they may cause epithelial damage. Identification of adult Paramphistomum, Calicophoron, Gastrothylax and Fischoederius at the species level based on morphology requires specialised expertise, whereas molecular genetic marker analysis is more precise and transferable. In the present study, we performed molecular characterisation of twenty seven adult flukes collected from the forestomachs of buffalo, cattle and goats in the Punjab province of Pakistan. PCR and sequencing of the ITS-2 rDNA region revealed a single haplotype in all cases. Phylogenetic comparison of P. epiclitum ITS2-rDNA sequences with those from other Paramphistomum, Calicophoron, Gastrothylax and Fischoederius species was performed to assess within and between species variation and validate the use of ITS-2 rDNA as a robust species-specific marker for P. epiclitum identification . This work provides a validated species-specific marker of P. epiclitum and the first report of this parasite species from Pakistan. The results of this study also have implications for the diagnosis and control of rumen flukes in the region and the need for accurate species identification to understand parasite distribution and population genetics. Graphical abstract: Highlights: Molecular confirmation of P. epiclitum using rDNA ITS-2 and the significance of its phylogenetic relationship to other fluke. Differentiation between Paramphistomum, Gastrothylax and Fischoederius as an aid to their identification in the rumen. The present study has important implications for the diagnosis and control of rumen flukes.